Análise elementar em carcinoma epidermoide de cavidade oral e sua relação com o tabagismo, expressão de genes de hipóxia e sobrevida - Archanjo, Anderson Barros (2018)
Head and neck cancer is a highly malignant and aggressive tumor type that presents a high rate of morbidity and mortality, mainly affecting the oral cavity, larynx and pharynx. The correlation between trace elements and the carcinogenesis process is due to the cytotoxic potential of some of these when available in excess concentrations. In addition to this, recent studies have described the association of these elements with the regulation of pathways related to tumor progression and the prognosis to be observed, among these pathways is the hypoxia pathway that has its main regulator HIF1. Thus, this work evaluated the elementary characterization in squamous cell carcinoma samples of the oral cavity, as well as the association of tobacco use in the elemental profile and the relation with the prognosis and survival of the patients. In addition, it evaluated the expression of the HIF1-α and PHD3 proteins and their relation to the smoking and alcohol habits, as well as the expression of these proteins to the presence of chemical elements in the same samples of squamous cell carcinoma of the oral cavity. For this, 78 samples of tumor tissue were obtained from patients diagnosed with squamous cell carcinoma of the oral cavity treated at the Arnaldo Vieira de Carvalho Cancer Institute and followed up for at least 24 months from initial treatment. The samples were categorized according to the smoking and alcohol habits. Tissue microarrays were made for elementary characterization using the synchrotron radiation-based μ-XRF technique, as well as for the analysis of the expression of HIF-1α and PHD3 proteins. The Chi-square test and the Fisher exact test were used for the association tests. Multivariate logistic regression by modeling was used to adjust odds ratios and confidence intervals. Survival curves were evaluated according to the Kaplan-Meier model and the Wilcoxon p-value and Cox Proportional Hazards model were used to adjust the hazards ratio values and the confidence interval. The following elements were detected: magnesium, phosphorus, sulfur, chlorine, potassium, calcium, chromium, manganese, iron, zinc, cobalt, nickel, copper, arsenic and bromine. Regarding the prognosis, magnesium was related to disease-free survival and chlorine and chromium with relapse, showing a protective factor against the occurrence of relapse and better disease-free survival. Nucleic HIF-1α expression was verified in 68 samples and cytoplasmic HIF-1α in 71 samples of oral cavity squamous cell carcinoma. Nuclear expression of PHD3 was observed in 49 samples and of cytoplasmic PHD3 in 48 samples. It was also verified the relation of the tumor size with the intensity of nuclear HIF-1α labeling and the positivity of the cytoplasmic PHD3 expression with the advanced clinical stage. It has also been shown that T3 / T4 tumors and the presence of chlorine increase the chances of presenting strong expression of cytoplasmic HIF-1α and that the clinical stage, the current consumption of alcohol and the presence of the chromium element influence the expression of PHD3. For survival, the association of disease-free survival with lymph node status was observed, while disease-specific survival was associated with lymph node status and advanced clinical stage. The present work was able to characterize oral squamous cell carcinoma samples for the presence of magnesium, phosphorus, sulfur, chlorine, potassium, calcium, chromium, manganese, iron, zinc, cobalt, nickel, copper, arsenic and bromine, of which the elements magnesium, chlorine, chromium, manganese, nickel, arsenic and bromine were associated with smoking. In addition, the chlorine and chromium elements were associated with the prognosis, in which the chlorine element was identified as an independent protective factor for recurrence and for better disease-free survival. Chromium, advanced clinical stage and alcohol consumption influenced the expression intensity of the PHD3 protein and the chlorine element and the tumor size of HIF-1α protein expression. This study presents unpublished data on the elemental profile, habits and expression of HIF-1α and PHD3 with the prognostic factors and survival of patients with squamous cell carcinoma of the oral cavity.